Investigation of cycling effect on the enhancement of electrochemical activity of zinc doped nickel oxide. (2023) - Chandra, Chaudhary Nitin; Rastogi, Chandresh Kumar; Gyanprakash, Maurya; Hari Krishna, R.; Manjunatha, C.
Abstract: Supercapacitor activity can be greatly influenced by the doping, conductivity, and the morphology of the electrocatalyst surface. Here, we are reporting the synthesis and characterization of undoped and zinc doped nickel oxide nanoparticles for investigating the influence of doping and cyclability on the supercapacitor activity using cyclic voltammetry (CV) measurements. We found that the activity of zinc doped NiO initially increases as per increase in number of CV cycles up to the fifty cycles and beyond this it decreases further. It is interesting to note that the cyclic voltammetry changes the morphology of the electrocatalyst surface, which enhances its activity. The polarization study of the fresh and cycled electrode showed the increase of Ni +3 content for the cycled electrode is responsible for the enhanced activity. Further, the impedance and galvanostatic charge discharge analysis showed that the pseudocapacitance of the cycled zinc doped electrode is higher than that of cycled nickel oxide electrode. Phenomenologically, the presence of Ni +3 and the increased electronic conductivity due to presence of zinc, with cyclic voltammetry cycling changes the energy of the surface, which increases the supercapacitor activity.